THE EFFECT OF PIGMENT ADDITION ON TRASH BAG MADE FROM RECYCLE HDPE - Rifan Gerby; Indri Hermiyati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Trash bag is a product of plastic film in the form of bubbles which is produced using extrusion blown film and coextrusion blown film machines. Trash bags have a variety of colors and sizes. The color of the trash bag comes from pigment additives. The addition of pigments to trash bags is not only to increase their aesthetic value, but can also have an impact on the mechanical properties and water resistance of finished goods. Therefore, experiments were carried out to make trash bags with variations in the addition of pigments (0%, 5%, 10%, 15%), HDPE recycle (60%), LLDPE recycle (40%), desiccant (5%). The experiment was conducted at PT Sang Plastik Indonesia. The purpose of the experiment was to find out the process of making trash bags, the exact formulation, and the mechanical properties and resistance to water. The process of making trash bags uses an extrusion blown film machine at a temperature of 190-195°C. The process of testing the mechanical properties consisting of tensile strength and tear strength was carried out six times for each trash bag sample using a universal testing machine, while the water resistance test was carried out by soaking each sample for 24 hours. The results of the trash bag tensile strength test with the addition of 0% pigment was 6.8 MPa, 5% pigment was 6.7 MPa, 10% pigment was 6.2 MPa, and 15% pigment was 6.1 MPa. The results of the tear strength test of the trash bag with the addition of 0% pigment was 1.8 N, 5% pigment was 1.7 N, 10% pigment was 1.6 N, and 15% pigment was 1.3 N. The results of the trash bag water resistance test with the addition of 0% pigment was 98.10%, 5% pigment is 99.13%, 10% pigment is 98.39%, and 15% pigment is 99.66%.